“OMAH TELO”: PENGEMBANGAN PRODUK BERBASIS UBI JALAR DI PROGRAM STUDI ILMU DAN TEKNOLOGI PANGAN - Siswanti Siswanti; R. Baskara Anandito; Bara Yudhistira (Universitas Sebelas Maret, 2017)
Tracer study which has been done by Department of Food Science andTechnology showed that only 62,5% of graduates have related job to the major, whilefrom 62,5% that have, only 10% become businessman/entrepreneur. This matternecessarily become a shared duty of the study program to escalate studententrepreneurial spirit since early on. Step that had been taken by the study program inorder to evoke student entrepreneurial spirit has not given maximum result becausestudents could not apply their sciene of entrepreneurship in a business unit practicedirectly. Therefore, Department of Food Science and Technology is commited to evokeand escalate student entrepreneurial spirit by forming a production unit named “OmahTelo”. This program is directed to obtain reveneu generating for the research group inparticular, Department of Food Science and Technology in general and also buildtechnopreneurship sprit in HIMAGHITA. In its first year, this program has beensuccessfully build up a productive business unit “Omah Telo” with chips and sweetpotato flour as the main products, also tela-tela, sweet potato stick, ice cream andschotel as the additional products. The entrepreneurship talkshow, food industrymanagement, and also marketing techniques have established the technopreneurshipspirit of the students. PIRT permission and online marketing could increase the productmarketing of IbPTK production.Keyword: omah telo, technopreneurship, sweet potato